Innovative Approaches to Combat Duck Viral Hepatitis: Dual-Specific Anti-DHAV-1 and DHAV-3 Yolk Antibodies - Siqi Lei; Yuanhe Yang; Chengchen Zhao; Anguo Liu; Pingli He (Vaccines)
Background and Objectives: Duck viral hepatitis (DVH), a highly contagious and acutely fatal avian disease, is characterized by convulsions, acute death, liver swelling, and hemorrhage, leading to substantial losses in the duck industry. However, there is no efficient prevention and control method for DHV infection. Duck hepatitis A virus (DHAV) is one of the primary pathogens responsible for DVH. Methods: In this study, we prepared a highly effective anti-DHAV IgY antibody by immunizing Hy-Line Brown laying hens at the peak of egg production. Results and Conclusions: The neutralization index of this antibody was found to be up to 38.90 (DHAV-1 QYD strain) and 141.25 (DHAV-3 GY strain) in vitro. The antibody also exhibited effective prophylactic effects in a model of hepatic inflammation following the viral challenge of ducklings, with a dose of 0.5 mL per duckling (containing 64 mg/mL of IgY) significantly reducing DHAV-related mortality by 66%, providing substantial protection against the infection. Furthermore, it effectively alleviated oxidative damage caused by DHAV in the ducklings. The results of this study indicate that IgY has the potential for treating DHAV infection; it also provides a new way for the treatment of poultry diseases with specific antibodies.